1973
DOI: 10.1084/jem.137.5.1180
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of the Immune Response

Abstract: The influence of immunization with (T,G)-A--L on the frequency and characteristics of [125I] (T,G)-A--L-binding cells (ABC) was investigated in high and low responder mice, whose ability to respond to (T,G)-A--L is under control of an H-2-linked immune response gene, Ir-1. Unimmunized high and low responder mice have about the same number of ABC in spleen and lymph nodes (6–12 ABC/104). However, after immunization with (T,G)-A--L in aqueous solution, ABC in high responders increase to a much greater extent tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Binding of soluble antigens by T cells has been particularly difficult to demonstrate and was thought to be due to a low site density of antigen-specific receptors in the T-cell membrane (1,2). It is more likely however, that the difficulty in demonstrating binding of soluble antigen by T cells is due to particular temperature and antigen concentration requirements requisite for antigen binding to occur (3,4).…”
mentioning
confidence: 99%
“…Binding of soluble antigens by T cells has been particularly difficult to demonstrate and was thought to be due to a low site density of antigen-specific receptors in the T-cell membrane (1,2). It is more likely however, that the difficulty in demonstrating binding of soluble antigen by T cells is due to particular temperature and antigen concentration requirements requisite for antigen binding to occur (3,4).…”
mentioning
confidence: 99%
“…Studies from 70s to 80s first showed the interference of HLA in direct the immunoglobulin production and responses to immunization [28][29][30][31][32]. In regard to test the capacity of different HLA in response to rLiD1 we immunized BC and C57 mice and also the transgenic mice with the protein adsorbed in MONTANIDE adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Dunham et al [5] found that the nonresponder mice to a linear random copolymer (L-Glu60 L-Ala30 L-Tyr10)n (GAT) had the same number of antigen-binding cells as the responder mice, as determined by an autoradiographic study of binding of GAT-125I to spleen cells. Hdmmerling et al [6] also reported that the high-responder and lowresponder mice to a branched, multichain polypeptide(T, G)-A--L had about the same number of antigen-binding cells both in the spleens and lymph nodes. According to Biozzi et al [2], the strain difference in antibody production against sheep erythrocytes (SRBC) between two strains of mice was found to be attributable principally to the difference in doubling times of cells engaged in antibody response rather than to different numbers of antigen-specific lymphocytes initiating the immune response.…”
Section: Discussionmentioning
confidence: 98%